Morphological Study of the Accommodative Apparatus in the Monkey Eye. Issue 3 (13th December 2014) - Hiraoka, Mari; Inoue, Kenichi; Senoo, Haruki; Takada, Masahiko
ABSTRACT For more than a century there has been debate concerning the mechanism of accommodation—whether the lens capsule or lens material itself determines the functional relationship between ciliary muscle contractility and lens deformation during refractive adaptation. This morphological study in monkey eyes investigates the composition and distribution of several connective tissue components in the accommodative apparatus relaying muscle force to lens organization. Elastin distributes on the marginal surface of the ciliary process. A zonule is composed of fibrillin produced by epithelial cells of the process. In the progress of extension over the posterior chamber, fibrils unite into strands and possess longitudinal plasticity. By induction of the elastin network, strands extend in a concentric direction covering the equatorial region of the capsule. Upon tethering to the lens, the strand ramifies into fibrils, penetrating deeply close to the epithelial layer of the lens and binding with the collagen of the intercellular spaces. Tight linkage of the zonule with the capsule transmits precise contractility. Inside the lens, the cortical layer's elastic connective tissue network forms widely spaced lamellae of crystalline fibers. In contrast, the central nuclear lamellae are tightly opposed. The accumulation of lamellae is greater in the anterior cortex than in the posterior, yielding a more variable anterior chamber depth in the visual axis. The plasticity of the zonule and connective tissue distribution inside the lens produces an adjustable configuration. Thus, tight linkage between the dynamism of the capsule with interaction of the lenticular flexibility provides a novel understanding of accommodation. Anat Rec, 298:630–636, 2015. © 2014 The Authors The Anatomical Record: Advances in Integrative Anatomy and Evolutionary Biology Published by Wiley Periodicals, Inc.